The extent of socio-economic empowerment among women in Malaba town council - Nafula, Vidah (Direct Research Journal of Social Science and Educational Studies, 2024)
The study set to establish the magnitude of ‘Programmatic functional skilling’ for socio-economic empowerment among women in Malaba Town Council. A cross-sectional survey design was adopted as a multimethod approach that can be blended with qualitative and quantitative data collection methods, correlation and descriptive approaches. This study adopted the use of interview schedules (guides), questionnaire and a focus discussion guide. The researcher organized the collected data according to the themes of the study, edited, coded and classified. Using the Statistical Package for Social Science (SPSS) Software version 22, data were also sorted and arranged according to the number of times that similar responses had occurred (frequencies) and percentages calculated, which formed the basis for correlation analysis that was used to establish the essential variables like the socio-economic empowerment of women and functional skilling, hence forming the basis for data interpretation, discussion, conclusions and recommendations. While in the aspect of literacy the women were doing fairly-well, things are not well in the line of leadership as well as other social engagements and contributions. This denotes a state of practically total lack of empowerment socially. Secondly, with fragile and ‘un-acceptable’ livelihoods for the most part (no income, no savings, no ownership of property, no access to financial services, then sex-working and drugs), the women of Malaba Town Council are economically not empowered at all. Therefore, the extent of socio-economic empowerment among women in Malaba Town Council is very low. The factors responsible for the low social and economic empowerment of women are mainly cultural and social. This is to say, the marginalization of women from a cultural point of view has led to their limitations in terms of education, ownership of property and leadership. It is clear that still not much has been done to address these two areas.